Witch in Miller's The Crucible as compared to Kramer and Sprenger's Malleus Maleficarum - Špatenková, Jana (Univerzita Pardubice, 2016)
Arthur Miller was a twentieth century American playwright who wrote a play The Crucible about witches and witch hunts in Salem as an allegory to the McCarthyism which was the period of the persecution of putative communists in America. Heinrich Kramer and Jacob Spreger were German inquisitors living in the late fifteenth century in Germany who wrote the treatise on the prosecution of witches Malleus Maleficarum, which encouraged people to the persecution of witches. The aim of this paper is to analyse in detail the portrayals of women and witches in Salem compared with the condemnatory attitude of the authors of Hammer of the Witches.
Čarodějnice v knize Čarodějky ze Salemu od Millera v porovnání s čarodějnicí v Kladivu na čarodějnice od Kramera a Sprengera
Keywords: Crucible; Miller, Arthur; Malleus Maleficarum; Hammer of the Witches; Kramer, Heinrich; Sprenger, Jacob; women; witches; witchcraft; Čarodějky ze Salemu; Kladivo na čarodějnice; ženy; čarodějnice; čarodějnictví